Effect of the serotonin transporter gene and of environment on the continuity of anxiety and depression traits throughout adolescence. (December 2014) - Nobile, M.; Greco, A.; Perna, G.; Colombo, P.; Bianchi, V.; Bellina, M.; Giorda, R.; Monzani, D.; Carlet, O.; Griez, E.; Molteni, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Aims. Many studies of various stress reactive phenotypes suggest that 5-HTTLPR short allele carriers (S-carriers) are characterised by the stable trait of negative affectivity that is converted to psychopathology only under conditions of stress. In this study, we examined the moderating role of the 5-HTTLPR on the relationship between two objective chronic risk factors, i.e. socioeconomic status (SES) and family structure, and internalising symptoms across adolescence. Methods. A multigroup path analysis was employed in a general adolescent population sample of a 5-year follow-up study. Results. Internalising problems were significantly more stable in the S-carriers. The focus on the main dimensions of internalising problems, i.e. anxiety and depression, revealed two different developmental patterns. In the S-carriers Anxiety problems seemed to be more stable and to predict a possible evolution towards the development of Depressive problems. In the long allele homozygotes (LL-subjects) the anxiety trait was significantly less stable, and, in late-adolescence, seemed to be significantly predicted by SES, suggesting a possible gene–environment interaction (G × E). Family structure seemed to play a role in a G × E perspective only until early-adolescence, while during late-adolescence SES seemed to play a pivotal role in interaction with 5-HTTLPR, with the S-allele playing a protective role. Conclusions. Future models of the developmental link between environmental adversities and internalising behaviour therefore need to consider that the effect of G × E interaction, may be associated with internalising behaviour via different mechanisms during different time frames and that shifts in the strength of this effect should be expected across development.